(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Evidenced by the rising popularity of smartphones, the advancement of mobile communication technology, and the widespread use of mobile social networks, mobile augmented reality (AR) has become a part of our daily lives. This study aims to understand the impact of AR-based beauty service app characteristics and spatial presence on user immersion. A survey of 731 Chinese and Korean users was conducted online, and the data were analyzed using SPSS 26.0. The findings reveal three factors that in AR-based beauty service apps significantly impact immersion in reality, interaction, and information availability. Additionally, spatial presence greatly influences immersion. Specifically, when Korean and Chinese consumers engage with AR beauty service apps, the sense of reality plays a crucial role. This research is expected to help businesses better grasp user psychology in providing AR-based beauty services, offer a realistic and compelling AR experience, enhance brand influence, and positively affect consumers’ purchasing decisions. It also aims to serve as foundational research data for the cosmetics industry to develop various marketing strategies using AR experiences tailored to consumer levels and behaviors in the future.